Geochemistry of Morts (HP2A) peat core from Canada - Nicole K Sanderson (PANGAEA, 2021)
Geochemistry data of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.